"Unpleasant accidents" of language affinity and literary translation (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
Investigating Russian (sporadically – Polish) translations of short stories by Vasyl Stefanyk this article represents "underwater reefs" while  translating the related languages.  It indicates that minor differences in grammatical and lexical levels become of great importance in mechanical interpreting Stefanyk's words and verbal images by means of chosen target languages.
Keywords: translation; Vasil Stefanik; the target language; language affinity; reality; idiomatics; dialect; reception